Prevalence of trigeminocervical convergence mechanisms in episodic and chronic migraine - Marco Antonio Takashi Utiumi; João Guilherme Bochnia Küster; Keryn Sporh Godk; Maria Luiza dos Santos; Bin Cheng Tan; Eldislei Mioto; Nikolai José Eustátios Kotsifas; Luiz Carlos Canalli Filho; Gabriel Eduardo Faria Colombani; Pedro André Kowacs; Elcio Juliato Piovesan (Arquivos de Neuro-Psiquiatria)
Abstract Background: Migraine pain location and trigeminocervical convergence have limited diagnostic value and have usually been assessed using non-standard verbal descriptors in a small number of centers. Objective: To use non-verbal descriptors of migraine pain location to determine the prevalence of trigeminocervical convergence mechanisms in patients with episodic and chronic migraine. In addition, we explored the factors associated with the presence of convergence. Methods: A multicenter study was carried out. The explicit pain location was explored by asking subjects to indicate, on an electronic form, three points on the anterolateral side and three points on the posterolateral side of the head and neck that represented the common locations of their migraine pain. We evaluated associations of the pain pattern with demographic and psychological features, comorbidities, lifestyle and other headache characteristics. Results: 97 episodic and 113 chronic migraine patients were included. Convergence was present in 116 migraineurs (55%) who indicated dominance of pain in the posterior cervical region. This site was more often involved in the chronic migraine group (21 vs. 33%; p=0.034). The number of migrainous/altered sensitivity symptoms (OR=1.39; 95%CI 1.14–1.71) was associated with convergence independently of the chronification status. In this symptom group, there were statistical associations between convergence and vomiting (p=0.045), tactile allodynia (p<0.001), nuchal rigidity (p<0.001) and movement allodynia (p=0.031). Conclusions: Trigeminocervical convergence is common in migraineurs and, in practice, it might be found frequently in chronic migraineurs. Some features commonly found in this group, such as altered sensitivity symptoms, are associated with this phenomenon.